Lentinula edodes Cultured Extract Intake at Puberty Mitigates Inflammatory Signals at the Mammary Glands by the Involvement of Epigenetic Mechanisms in BALB/c Mice. - Yasavoli-Sharahi, Hamed; Shahbazi, Roghayeh; Alsadi, Nawal; Sahebi, Nasim Bondar; Cuenin, Cyrille; Cahais, Vincent; Chung, Felicia Fei-Lei; Herceg, Zdenko; Matar, Chantal; Wani, Imtiaz (Breast Journal, 2026)
Exposure to immune stress or lipopolysaccharide (LPS) during critical developmental stages like puberty may lead to gut microbiome dysbiosis and epigenetic dysregulation in mammary glands, affecting gene expression and potentially elevating breast cancer susceptibility in adulthood. Although LPS's adverse impacts on intestinal and brain functions are well‐documented, its effects on mammary glands remain underexplored. Using an immunocompetent BALB/c mouse model, we administered an acute LPS dose (1.5 mg/kg body weight) during puberty. The study evaluated the long‐term consequences of LPS exposure alone and combined with AHCC (Lentinula edodes cultured extract, 2 g/kg body weight/day) on DNA methylation patterns, cytokine profiles, and microRNA expression in mammary glands at 9 weeks of age. Analyses included DNA methylation sequencing, multiplex immunoassays, quantitative PCR, and image processing. Pubertal LPS exposure produced persistent molecular dysregulation in mammary glands, including differential DNA methylation (> 5% change vs. control; FDR‐adjusted p < 0.05), elevated inflammatory mediators, and altered microRNA expression. Differentially methylated regions were enriched in regulatory features, with decreased methylation at transcription start sites, promoters, and 5′ UTRs of genes implicated in mammary development and oncogenic signaling (including Vav3, Pdgfa, Pdgfc, Jag2, Hras, Ksr1, Il2rb, Il17b, and Il17rb) in the LPS group, whereas the AHCC + LPS group exhibited a shift toward hypermethylation at these loci (approximately 5%–10% decrease). Inflammatory profiling showed increased IL‐17A/F (∼2‐fold vs. control; p < 0.05), while microRNA analyses indicated reduced let‐7a/c (∼30% vs. control; p < 0.05). Notably, miR‐130a and miR‐34a increased ∼1.5‐fold across all treatment groups relative to control. Pubertal LPS exposure induces enduring epigenetic and inflammatory changes in mammary glands that may heighten breast cancer risk. AHCC's mitigating role indicates potential for dietary interventions to counteract these effects.